Impact Of Human Resources Management Practices On Turnover Intention Among Hotel Employees In Amman, Jordan - Mohd, Maqableh Omar Aref (2024)
This study determines the relationship between HRM practices and turnover intention among five-star hotels in the Jordanian capital, Amman. This study investigated also the mediating effect of job satisfaction on the connection between HRM practices and turnover intention in addition to the moderation impact of employee innovative behavior on the relationship among the HRM practices and employee turnover intention, in addition to the moderating influence of employee innovative behavior on the connection between job satisfaction and turnover intention.